2012
DOI: 10.1016/j.matlet.2011.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of photo induced mass transfer in amorphous chalcogenide films

Abstract: Any queries or remarks that have arisen during the processing of your manuscript are listed below and highlighted by flags in the proof. Please check your proof carefully and mark all corrections at the appropriate place in the proof (e.g., by using onscreen annotation in the PDF file) or compile them in a separate list.For correction or revision of any artwork, please consult http://www.elsevier.com/artworkinstructions.Any queries or remarks that have arisen during the processing of your manuscript are listed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The excitation of electron-hole pairs, defect creation, bond braking and rearrangement always are present in these amorphous semiconductor materials under illumination with photons or electron beam. As a result of this, the sample possesses increased free volume [8] and plasticity [9] , which plays important role in the relatively small (about 0.5-1%) local expansion effect in irradiated spots, but also influences essentially larger local surface (thickness) changes due to the stimulated mass-transport in the gradient fIelds of excitation [7,9,10]. The elastic moduli were determined from the average of the fitted parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The excitation of electron-hole pairs, defect creation, bond braking and rearrangement always are present in these amorphous semiconductor materials under illumination with photons or electron beam. As a result of this, the sample possesses increased free volume [8] and plasticity [9] , which plays important role in the relatively small (about 0.5-1%) local expansion effect in irradiated spots, but also influences essentially larger local surface (thickness) changes due to the stimulated mass-transport in the gradient fIelds of excitation [7,9,10]. The elastic moduli were determined from the average of the fitted parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The PI self-diffusion coefficients, D, were measured in As 20 Se 80 films at room temperature at various light intensities. It was found that D linearly increased with the intensity, I, and the coefficient β=D/I was equal 2.5×10 −18 m 4 /J [22]. Later, the PI diffusion coefficients were quantitavely estimated by the kinetics of growth of surface relief gratings (SRGs) at 77 and 300 K [23] for the same film composition, and recently, the PI coefficients were measured [24] in these films in a wide temperature range (308-398 K) and light intensities (0-2.5 W/cm 2 ).…”
Section: Basic Data On Pi Diffusion Coefficientsmentioning
confidence: 96%
“…The first quantitative measurements of PI diffusion coefficients data were obtained using a method based on the theory of capillary flattening of solids [21], which was modified [22] by taking into account the final thickness of Any further distribution of this work must maintain attribution to the author(s) and the title of the work, journal citation and DOI. the films.…”
Section: Basic Data On Pi Diffusion Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…For diffusion mechanism κΛ3, whereas for viscous flow κΛ1 and due to this difference, one can determine the flattening mechanism. Measurements of the flattening kinetics under band gap light illumination at room temperature for SRGs of various periods produced on the surface of As 20 Se 80 ACFs showed that the main mechanism is PI bulk diffusion.…”
Section: Introductionmentioning
confidence: 99%